Data Processing Approach Based on OPC UA Architecture Implementation and Bluebird Platform - Marek Vagas; Ondrej Majercak; Alena Galajdova; Robert Rakay; Jaroslav Romancik (IEEE Access)
Process flexibility of automated workplaces, lines, and machinery is essential for optimizing, digitalizing and deploying critical principles based on IoT, IIoT and Industry 4.0/5.0. This potential also has considerable overlap and impetus in manufacturing and non-manufacturing areas. In addition, national and international directives, norms and standards are putting pressure on corporate structures to deploy these principles as much as possible. Therefore, the authors of this paper focused on creating an architecture for collecting, evaluating and sorting (process and state) data from a monitored automated workplace in such a way as to transform the existing research knowledge from a comprehensive solution that will be of significant benefit to both the scientific community and industrial practice. The proposed approach is based on implementing the OPC UA technology, the selected IBH Link UA communication gateway and the Bluebird visualization platform. By realizing measurements, tests, and remote management via dashboard windows, the paper intends to contribute a concrete example to the advanced supervision of the monitored running processes of automated lines and workplaces (at SCADA level and above). The requirements were seamless connectivity, immediate response and advanced diagnostics of the monitored processes. The universal language the authors want to communicate is the OPC UA structure, which unifies and prepares other solutions supporting MQTT protocols. As a result, we documented the performance of our approach in the range of 0.58 - 0.61 for the Capability Index (CpK) and 0.58 - 0.63 for the Capability Process (Cp) value. We uncovered potential opportunities for improving process and workplace consistency (stability). The paper’s parallel and supporting idea is to combine known (and working-proven) approaches without costly software and hardware replacement of the entire automated workplace equipment portfolio.